Caveolin-1/PPARα axis suppresses T follicular helper cell response in primary Sjögren disease - Sulan Yu; Meiling Wu; Weizhen Zeng; Weiwei Fu; Yacun Chen; Jing Xie; Philip Hei Li; Yun Feng; Jiangang Shen; Xiang Lin (Cell Reports)
Summary: T follicular helper (Tfh) cells play a central role in humoral autoimmunity, including primary Sjögren disease (SjD). However, targeting Tfh cells in clinical management is challenging. Previous studies suggest that inducible T cell co-stimulator (ICOS) directs Tfh cell motility in engaging bystander B cells and promoting plasma cell differentiation. Herein, we took advantage of the mouse model of experimental Sjögren syndrome (ESS) and identified an unappreciated role of caveolin-1 (Cav-1) in suppressing ICOS expression in Tfh cells and SjD pathogenesis. Peroxisome proliferator-activated receptor alpha (PPARα), a transcription factor downstream of Cav-1, rapidly repressed Icos transcription upon Tfh polarization, independent of lipid metabolism. Both Cav-1 and PPARα were decreased in CD4+ T cells from patients with SjD and ESS mice. Notably, the pharmaceutical agonist of PPARα suppressed human and murine Tfh cell responses both in vitro and in vivo and effectively ameliorated the disease pathology of ESS mice with chronic inflammation.